Achromatic Huygens' Metalenses with Deeply Subwavelength Thickness. Issue 22 (3rd September 2020) - Fathnan, Ashif A.; Liu, Mingkai; Powell, David A.
Abstract: Matching magnetic and electric responses has proven key to achieving high‐efficiency transmissive Huygens' metasurfaces. However, the complex frequency dependence of the required magnetic and electric responses is difficult to control, causing inevitable mismatch and undesired narrowband responses. Here, a rigorous design methodology is proposed to obtain a metasurface in which the Huygens' condition is maintained over a broad bandwidth and range of phase tuning. By utilizing three patterned metallic layers separated by dielectrics, it is shown how the resonant modes with electric and magnetic dipole moments can be controlled almost independently, enabling broadband transparency with controllable dispersion. Representing the resonant elements as series and parallel inductance–capacitance configurations, a convenient implementation of a macro‐level design into a realistic geometry is demonstrated. Based on the proposed method, a subwavelength thickness metasurface lens that maintains constant focal length over 11% of fractional bandwidth is designed and characterized. It is also shown that the method can be utilized to achieve specified values of chromatic dispersion of a metasurface lens, enabling various functional devices and applications. Abstract : Huygens' metasurfaces are widely adopted to enable high‐efficiency subwavelength optical devices. However, current procedures to realize metallic Huygens' metasurfaces typically lead to very narrowband performance. In this paper, a rigorous design methodology to broaden the operational bandwidth of Huygens' metasurfaces is presented, along with an experimental demonstration of an achromatic Huygens' metalens in the microwave regime.